(Dis)Joining Fitness Gyms Membership: Sustained Participation and Deterred Mindset amongst Female Teachers in Singapore - Vernetta Xinn Yinng Phang; Ho Jin Chung (Asian Society of Kinesiology, 2020)
OBJECTIVES The purpose of this study was to examine the key decision making elements of why female teachers join and disjoin a fitness gym membership. METHODS The participants of the study comprised of ten healthy female teachers, aging from 34 to 45. Out of the ten participants, five of them were members of fitness gyms while five of them were non-members of fitness gyms. A semi-structured interview was conducted with each participant. Each interview was audiorecorded, before being transcribed verbatim. A thematic analysis approach was used for data analysis and higher-order themes were identified for each group of participants. RESULTS The key elements to sign up for a gym membership included keeping body and mental health, group synergy and peer influence, instructors' guidance and convenience of gym facilities. The key elements for deterrence included the high cost of membership, lack of time, dislike for long term commitment and inconvenience of schedule. CONCLUSIONS The study discusses the controllable and uncontrollable factors associated with signing up for a gym membership including, the cost of membership and the occupations of teachers such as working hours and teachers' circumstances. The results of this study enable gym operators to better understand how to cater and engage a specific target audience.